2005
DOI: 10.5194/hess-9-692-2005
|View full text |Cite
|
Sign up to set email alerts
|

The role of Lake Dongting in regulating the sediment budget of the Yangtze River

Abstract: Lake Dongting, the second largest freshwater lake in China and located in the middle reaches of the River Yangtze catchment, was formed at the beginning of the Holocene period by sea level rise and has varied in size with changes in local weather patterns. The sedimentation rate in Lake Dongting during the Holocene is about 50×10 6 m 3 yr 1 , or 80×10 6 t yr 1 (a sand bulk density of 1.6×10 3 kg m -3 ), given the sediment deposition rate as 10 mm yr 1 and the average lake size as 5000 km 2 . By comparing the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 14 publications
4
25
0
Order By: Relevance
“…A correlation analysis showed a statistically significant correlation between the mean water level from July to August and the mean TSM from 1978 to 2013, with a correlation coefficient (r) of 0.79, 0.86 and 0.58, respectively, for WDL, EDL and SDL ( Figure 6). The result was similar to the findings of many previous studies [24,[54][55][56]] that have suggested that water level could affect lake area variation, sediment charge and other environmental conditions in Dongting Lake. The r for WDL was 0.79, which represents a significant correlation (p < 0.05, with t-test).…”
Section: Factors Affecting the Spatial And Temporal Changes In Tsmsupporting
confidence: 82%
“…A correlation analysis showed a statistically significant correlation between the mean water level from July to August and the mean TSM from 1978 to 2013, with a correlation coefficient (r) of 0.79, 0.86 and 0.58, respectively, for WDL, EDL and SDL ( Figure 6). The result was similar to the findings of many previous studies [24,[54][55][56]] that have suggested that water level could affect lake area variation, sediment charge and other environmental conditions in Dongting Lake. The r for WDL was 0.79, which represents a significant correlation (p < 0.05, with t-test).…”
Section: Factors Affecting the Spatial And Temporal Changes In Tsmsupporting
confidence: 82%
“…(Dai et al 2005;Yang et al 2006Yang et al , 2014Hu et al 2009). Dongting Lake, which drains into the middle part of the mainstream, has played an important role in the sediment budget of the Yangtze (Dai et al 2005). In particular, below the Three Gorges, turbid water from the upper part flows not only into the mainstream of the Yangtze but also into channels flowing into Dongting Lake, known as the Three Outlets (Dai et al 2005;Yin et al 2007).…”
Section: Hydrologic Settingmentioning
confidence: 99%
“…The Dongting Lake drainage, with an area of 2.7 × 10 5 km 2 (Hayashi et al 2008), gathers waters from four major tributaries. In addition, three natural channels flow from the mainstream into Dongting Lake, known as the "Three Channels" or "Three Outlets" (Dai et al 2005;Yin et al 2007). Thus, some water and SPM in the upper part of the mainstream flow into Dongting Lake through these three channels (Dai et al 2005).…”
Section: Geographical Settingmentioning
confidence: 99%
See 2 more Smart Citations